Hydrophobically associated polymers for wettability alteration and enhanced oil recovery – Article review - A.N. El-hoshoudy; S.E.M. Desouky; M.Y. Elkady; A.M. Al-Sabagh; M.A. Betiha; S. Mahmoud (Egyptian Journal of Petroleum)
Crude oil and other petroleum products are crucial to the global economy today due to increasing energy demand approximately (∼1.5%) per year and significant oil remaining after primary and secondary oil recovery (∼45–55% of original oil in place, OOIP), which accelerates the development of enhanced oil recovery (EOR) technologies to maximize the recovered oil amount by non-conventional methods as polymer flooding. This review discusses enhanced oil recovery methods specially polymer flooding techniques and their effects on rock wettability alteration.